Evaluation of the impacts of insulin on ovulation in Nigerian women with polycystic ovarian syndrome: a cross-sectional sonographic study - Ezugwu, Emmanuel E.; Ugwu, Anthony C.; Manafa, Patrick O.; Ezugwu, Gloria I. (International Journal of Advances in Medicine, 2022)
Background: Insulin resistance (IR) is a metabolic state characterized by a decrease in cellular ability to respond to insulin signaling, which contribute to pathophysiological mechanism in the development of all metabolic complication of polycystic ovary syndrome (PCOS). The aim of the study was to match categorized values of patient’s biochemical predisposing factors for polycystic ovaries such as insulin with change in follicular sizes as determined by sonography following CLOMID inducement therapy. Methods: This experimental study was carried out in Anambra State, Nigeria from June 2018 to May 2021. Those included in the study were women of child bearing age (18 to 45 years) for both groups. The ultrasound examinations and insulin levels measurements were performed on each subject and data such as follicular sizes, insulin levels before and after treatment were recorded. Obtained data were analyzed using both descriptive and inferential statistical tools. Results: There were no statistically significant mean differences in the insulin levels (t=1.16, p=0.81) and maximal follicular size (t=0.39, p=0.70) of women with and without polycystic ovary who had successful and failed ovulation before the clomid treatment. Both the insulin level (t=2.85, p<0.01) and follicular size (t=4.88, p<0.01) showed statistically significant mean differences. There was significant difference in insulin (F=7.55, p<0.01), with the control having the lowest insulin concentration. Conclusions: There were statistically significant mean differences in the insulin level and follicular size in women with polycystic ovary after clomid treatment. Therefore, clomiphene citrate inducement triggers increase in serum concentration of insulin.